New Cosmopolitanisms, Race, and Ethnicity. Cultural Perspectives - Luczak, Ewa Barbara (De Gruyter, 2019)
This anthology sheds new light on cosmopolitanism and culture in the contemporary world. Drawing on postcolonial, ethnic, and critical race studies as well as recent literary and critical theory, it demonstrates that new cosmopolitan thinking can embrace an awareness of ethnic and local differences. It disputes the utopianism of colorblind universalism and argues for the persistence of "race" and racialized thinking in lived experience. The essays collected in this volume valorize minoritarian perspectives and urge readers to rethink cosmopolitanism from the perspective of the underprivileged and marginalized and highlight the role of culture in mobilizing social empathy and solidarity with the world's precariat. The contributors, who come from over a dozen different countries and from diverse socio-cultural backgrounds, constitute a vibrant cosmopolitan community in itself.